2021
DOI: 10.15376/biores.16.3.5450-5466
|View full text |Cite
|
Sign up to set email alerts
|

Natural cellulosic material characteristics: A possibility to develop antimicrobial active fiber-based packaging

Abstract: Coconut husk, rubberwood sawdust, and palm leaf base are cellulosic agricultural wastes that have potential to be processed to fiber as absorbing material. This study investigated characteristics (morphological, physiological properties, chemical composition, absorption capacity, and water absorption isotherms) of coconut, rubberwood, and palm fiber. Also, the study aimed to develop an antimicrobial sachet packaging to resist against foodborne pathogens (Listeria monocytogenes, Staphylococcus aureus, Salmonell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The rubberwood sawdust was able to absorb the orange oil emulsion with a maximum level of 0.5 g/g at the equilibrium point (120 min). The result of this study corresponds with that of Parichanon et al (2021), where they reported that the rubberwood sawdust could also absorb lime oil emulsion and Litsea cubeba oil emulsion at 30% to 40%. This is confirmed to produce an orange oil sachet by dipping the sawdust for 120 min in orange oil emulsion.…”
Section: Emulsion Absorption Capacity Of Rubberwood Sawdustsupporting
confidence: 89%
See 1 more Smart Citation
“…The rubberwood sawdust was able to absorb the orange oil emulsion with a maximum level of 0.5 g/g at the equilibrium point (120 min). The result of this study corresponds with that of Parichanon et al (2021), where they reported that the rubberwood sawdust could also absorb lime oil emulsion and Litsea cubeba oil emulsion at 30% to 40%. This is confirmed to produce an orange oil sachet by dipping the sawdust for 120 min in orange oil emulsion.…”
Section: Emulsion Absorption Capacity Of Rubberwood Sawdustsupporting
confidence: 89%
“…Rubberwood sawdust can efficiently adsorb essential oil. Additionally, its high adsorption capacity, reusability, and low cost make it suitable for large-scale applications (Parichanon et al 2021). It is necessary to assess the effects of ripening regulators together with techniques that regulate the control of mould growth during transportation and storage of the mangosteens.…”
Section: Introductionmentioning
confidence: 99%